1979
DOI: 10.1172/jci109283
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Parathyroid Hormone and Its Fragments in Rat Tissues

Abstract: A B S T R A C T After intravenous injection of [125LI]iodo-parathyroid hormone in the rat, uptake of the hormone was greatest in the liver and kidneys. Uptake was rapid, reaching a maximal concentration by 4 and 8 min, respectively. Extracts, prepared from both these organs at intervals soon after the injection of intact hormone, showed three main radioactive peaks when samples were subjected to gel filtration under proteindenaturing conditions. The first peak coeluted with intact hormone.The second eluted at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1980
1980
2000
2000

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Additionally, since in native PTH position 34 is followed by several hydrophobic residues, which probably draw this region of the molecule more tightly into the hydrophobic core of the NH2-terminal domain, the possible existence of natural forms of PTH even more active than the 1-34 peptide should be considered. Such fragments may in fact be generated in vivo by the reported cleavages at positions 37 and 39 (25), and it may be that this region (residues 34-39) is of major significance in producing the most active conformation of PTH and its natural fragments. Both theoretical calculations in this paper predict a particularly exposed portion of the chain at positions 37-40, and this may provide a rationale for the known in vivo cleavage of PTH in this region.…”
mentioning
confidence: 99%
“…Additionally, since in native PTH position 34 is followed by several hydrophobic residues, which probably draw this region of the molecule more tightly into the hydrophobic core of the NH2-terminal domain, the possible existence of natural forms of PTH even more active than the 1-34 peptide should be considered. Such fragments may in fact be generated in vivo by the reported cleavages at positions 37 and 39 (25), and it may be that this region (residues 34-39) is of major significance in producing the most active conformation of PTH and its natural fragments. Both theoretical calculations in this paper predict a particularly exposed portion of the chain at positions 37-40, and this may provide a rationale for the known in vivo cleavage of PTH in this region.…”
mentioning
confidence: 99%
“…The plasma samples taken at various times following single injections of both b-PTH 1-84 and oxidized b-PTH 1-84 into dogs, were subjected to gel permeation chromatography using Bio-gel P-100 (Bio-Rad Laboratories, Richmond, Calif.). The (3,17). In fact, Neuman et al (3), using radiolabeled intact PTH by a technique reported to preserve biological activity, demonstrated increasing hepatic PTH uptake associated with increasing biological activity of the hormone.…”
Section: Methodsmentioning
confidence: 99%
“…The metabolism of the hormone is thought to be rapid, judging from the rapid initial rates of disappearance of PTH following its addition to the circulation (1,3,15,16 (3,17). The liver has been identified as having the greatest uptake rate for intact hormone (3,9,17). Studies by D'Amour et al (17) suggest that most of hepatic PTH uptake is localized to Kupffer cells, and that hepatic cleavage of intact PTH and production of C-terminal fragments can be attributed to this cell type.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One reason for the reduced activity of hPTH-(28-48) could be less resistance to circulating and/or cellular proteases. The main PTHmetabolizing activity has been ascribed to the Kupffer cells (macrophages) of the liver, where a cathepsin D-like activity appears to be responsible for the degradation of the hormone [36,37]. Metabolism of PTH has also been shown to occur by cathepsin D action within the endosomes of alveolar macrophages [38].…”
Section: Introductionmentioning
confidence: 99%